ACTIVE SOURCE ROUTING PROTOCOL FOR MOBILE NETWORK: (International Journal of Engineering and Computer Science, 2017)
An ad-hoc mobile network is a collection of mobile nodes that are dynamically and arbitrarily located in such a manner that the interconnections between nodes are capable of changing on a continual basis. The primary goal of such an ad-hoc network routing protocol is correct and efficient route establishment between a pair of nodes so that messages may be delivered in a timely manner. LAR is an on-demand protocol who is based on the DSR(Dynamic Source Routing). The Location Aided Routing protocol uses location information to reduce routing overhead of the ad-hoc network! Normally the LAR protocol uses the GPS(Global Positioning System) to get these location information’s. With the availability of GPS, the mobile hosts knows there physical location.Ad hoc networks are a new wireless networking paradigm for mobile hosts. Unlike traditional mobile wireless networks, ad hoc networks do not rely on any fixed infrastructure. Instead, hosts rely on each other to keep the network connected. The military tactical and other security-sensitive operations are still the mainapplications of ad hoc networks, although there is a trend to adopt ad hoc networks for commercial uses due to their unique properties. One main challenge in design of these networks is their vulnerability to security attacks. In this paper, we study the threats an ad hoc network faces and the security goals to be achieved. We identify the new challenges and opportunities posed by this new networking environment and explore new approaches to secure its communication. In particular, we take advantage of the inherent redundancy in ad hoc networks — multiple routes between nodes — to defend routing against denial of service attacks.